COMPARATIVE RESEARCH OF CUSTOMER EXPERIENCE AND CUSTOMER EXPECTATION BETWEEN MALE AND FEMALE CUSTOMERS OF KM. MAJESTIC KAWANUA - Sabanari, Anatasya E.; Lambey, Linda .; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: Sea transportation is one of the most indispensable transportation of Indonesian society.KM. Majestic Kawanua operating in Indonesian sea areas, especially in North Sulawesi area. There are two main objectives that will be achieved, which are: To determine the significant difference of customer experience between male and female customers of KM. Majestic Kawanua and To determine the significant difference of customer expectation between male and female customers of KM. Majestic Kawanua. Therefore customer experience and customer expectation will greatly affect to customer satisfaction. This research conducted by a quantitative method and this research population is the customers of KM. Majestic Kawanua. By using an Independent Sample t-test, this research conducted a hypothesis is significant difference in customer experience and customer expectation between male and female customers of KM. Majestic Kawanua. Based on the result of this research, the data is normally distributed. The result shows that there are no significant differences in customer satisfaction based on customer experience and customer expectation between male and female customers of KM. Majestic Kawanua. Findings suggest KM. Majestic Kawanua employes to be quick in responding to customer needs so that customers feel satisfied using the KM. Majestic Kawanua services.Keywords:customer experience, customer expectation, gender.